2019
DOI: 10.1002/cphc.201900411
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Gold(I) Diarylallenylidene Complexes: Bonding Features and Ligand Effects

Abstract: Using computational approaches, we qualitatively and quantitatively assess the bonding components of a series of experimentally characterized Au(I) diarylallenylidene complexes (N.Kim, R.A.Widenhoefer, Angew. Chem. Int. Ed . 2018 , 57 , 4722–4726). Our results clearly demonstrate that Au(I) engages only weakly in π‐backbonding, which is, however, a tunable bonding component. Computationally identified trends in bonding are clearly correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…It has been also suggested that the electronic properties (and in particular the π‐accepting power) of NHC‐metal compounds could be efficiently probed via NMR spectroscopy [103] . Moreover, we have recently demonstrated that the extent of the π communication in gold(I) diarylallenylidene compounds tightly correlates with the experimental 13 C NMR chemical shifts [58] . In the present case, NMR 13 C chemical shifts of the two carbon atoms of the alkynyl may be in principle shielded and deshielded by different bonding mechanisms and in particular by the π communication between the alkynyl ligand and the metal fragment.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…It has been also suggested that the electronic properties (and in particular the π‐accepting power) of NHC‐metal compounds could be efficiently probed via NMR spectroscopy [103] . Moreover, we have recently demonstrated that the extent of the π communication in gold(I) diarylallenylidene compounds tightly correlates with the experimental 13 C NMR chemical shifts [58] . In the present case, NMR 13 C chemical shifts of the two carbon atoms of the alkynyl may be in principle shielded and deshielded by different bonding mechanisms and in particular by the π communication between the alkynyl ligand and the metal fragment.…”
Section: Resultsmentioning
confidence: 85%
“…[103] Moreover, we have recently demonstrated that the extent of the π communication in gold(I) diarylallenylidene compounds tightly correlates with the experimental 13 C NMR chemical shifts. [58] In the present case, NMR 13 C chemical shifts of the two carbon atoms of the alkynyl may be in principle shielded and deshielded by different bonding mechanisms and in particular by the π communication between the alkynyl ligand and the metal fragment. The π donation component possesses two essential features: i) an increase of π communication extent causes, in principle, the two carbon atoms to be deshielded and ii) π communication shows a variability along the series, suggesting that for the complexes with larger π donation an appreciable deshielding on the two carbon atoms should be observed.…”
Section: Experimental Observables/bonding Features Relationshipmentioning
confidence: 77%
See 2 more Smart Citations
“…We chose to employ intrinsic bond orbitals (IBOs) to generate localized bond orbitals. They are physically equivalent to the canonical molecular orbitals but give an intuitively understandable picture of bonding situations that has been shown to describe both the Lewis contributions and the relevant delocalization contributions well. …”
Section: Resultsmentioning
confidence: 99%